A qualitative study of DevOps usage in practice. Issue 6 (June 2017) - Erich, F. M. A.; Amrit, C.; Daneva, M.
Abstract: Organizations are introducing agile and lean software development techniques in operations to increase the pace of their software development process and to improve the quality of their software. They use the term DevOps, a portmanteau of development and operations, as an umbrella term to describe their efforts. In this paper, we describe the ways in which organizations implement DevOps and the outcomes they experience. We first summarize the results of a systematic literature review that we performed to discover what researchers have written about DevOps. We then describe the results of an exploratory interview‐based study involving 6 organizations of various sizes that are active in various industries. As part of our findings, we observed that all organizations were positive about their experiences and only minor problems were encountered while adopting DevOps.